ANALYSIS OF TEACHER READINESS AND PERFORMANCE IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM - Reza, Reza Okrianti; Aufa, Aufa (JP (Jurnal Pendidikan) : Teori dan Praktik, 2024)
This research provides an overview of teachers’ readiness to implement the Independent Curriculum in elementary schools and what they are doing and preparing. The place of this research is SDN 08 Ranah Batahan which is located in Batahan, Kec. Batahan Realm, West Pasaman Regency, West Sumatra. This research uses a qualitative approach, with qualitative phenomenology as the type of approach chosen. This research data was obtained through document study and observation and interviews as the main data. Elementary school teachers at SDN 08 Ranah Batahan class I and IV were informants for this research. In this research, the data analysis method consists of three stages: data reduction, data presentation, and data verification. The research results show that SDN 08 Ranah Batahan teachers are ready to implement the independent curriculum. This is shown by the fact that teachers try to convey values ​​related to their understanding of the implementation of the independent curriculum, starting from understanding the concepts, objectives, mechanisms and structure of implementing the independent curriculum; second, teachers have learned more about preparation and planning the learning process; and third, the teacher has implemented appropriate methods. Based on the research results, it can be concluded that teachers at SDN 08 Ranah Batahan are trying their best to prepare for the implementation of the independent curriculum in elementary schools.